2016
DOI: 10.3389/fphys.2016.00459
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the In vitro and In vivo Effects of Asparagopsis taxiformis Bioactive Phycoderivates on Teleosts

Abstract: Several compounds from marine organisms have been studied for their potential use in aquaculture. Among the red algae, Asparagopsis taxiformis is considered one of the most promising species for the production of bioactive metabolites with numerous proposed applications. Here, the in vitro antibacterial activity, the easy handling and the absence of adverse effects on marine fish species are reported. Depending on the seasonal period of sampling, ethanol extracts of A. taxiformis exhibited significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…In a study evaluating the effect of the alga Sargassum ilicifolium in the diet of a sturgeon (Huso huso), it was found that supplying algae at the concentration of 10% of the diet increased the number of WBCs, with an increase in the numbers of neutrophils and a decrease in the number of lymphocytes [46]. In sea bream (Sabanejewia aurata) fed with the alga Asparagopsis taxiformis and its extract, significant decreases (p < 0.05) in RBC counts, Hb, Ht, and WBC counts were found [47]. That study's authors suggested that the inclusion of algae in the diet had negative effects on hematological parameters, which could be related to a dose/response effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the effect of the alga Sargassum ilicifolium in the diet of a sturgeon (Huso huso), it was found that supplying algae at the concentration of 10% of the diet increased the number of WBCs, with an increase in the numbers of neutrophils and a decrease in the number of lymphocytes [46]. In sea bream (Sabanejewia aurata) fed with the alga Asparagopsis taxiformis and its extract, significant decreases (p < 0.05) in RBC counts, Hb, Ht, and WBC counts were found [47]. That study's authors suggested that the inclusion of algae in the diet had negative effects on hematological parameters, which could be related to a dose/response effect.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and in vitro cytotoxic activity of extracts prepared using methanol, chloroform, petroleum ether and ethyl acetate from red alga Asparagopsis taxiformis were demonstrated [ 13 ]. In another study, ethanol extract significantly exhibiting antibacterial activity against fish pathogenic bacteria was found [ 14 ]. Ethanolic extract of brown alga, Padina pavonica having antimicrobial, antioxidant, and anticancer activities was proved [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, fish nutrition and its effect to animal health is an important new field of study in the aquaculture industry (Lo Cascio et al, 2018;Marino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%